Metal ion concentrations in body fluids after implantation of hip replacements with metal-on-metal bearing--systematic review of clinical and epidemiological studies. - Albrecht Hartmann; Franziska Hannemann; Jörg Lützner; Andreas Seidler; Hans Drexler; Klaus-Peter Günther; Jochen Schmitt (PLoS ONE, 2013)
Introduction The use of metal-on-metal (MoM) total hip arthroplasty (THA) increased in the last decades. A release of metal products (i.e. particles, ions, metallo-organic compounds) in these implants may cause local and/or systemic adverse reactions. Metal ion concentrations in body fluids are surrogate measures of metal exposure. Objective To systematically summarize and critically appraise published studies concerning metal ion concentrations after MoM THA. Methods Systematic review of clinical trials (RCTs) and epidemiological studies with assessment of metal ion levels (cobalt, chromium, titanium, nickel, molybdenum) in body fluids after implantation of metalliferous hip replacements. Systematic search in PubMed and Embase in January 2012 supplemented by hand search. Standardized abstraction of pre- and postoperative metal ion concentrations stratified by type of bearing (primary explanatory factor), patient characteristics as well as study quality characteristics (secondary explanatory factors). Results Overall, 104 studies (11 RCTs, 93 epidemiological studies) totaling 9.957 patients with measurement of metal ions in body fluids were identified and analyzed. Consistently, median metal ion concentrations were persistently elevated after implantation of MoM-bearings in all investigated mediums (whole blood, serum, plasma, erythrocytes, urine) irrespective of patient characteristics and study characteristics. In several studies very high serum cobalt concentrations above 50 µg/L were measured (detection limit typically 0.3 µg/L). Highest metal ion concentrations were observed after treatment with stemmed large-head MoM-implants and hip resurfacing arthroplasty. Discussion Due to the risk of local and systemic accumulation of metallic products after treatment with MoM-bearing, risk and benefits should be carefully balanced preoperatively. The authors support a proposed "time out" for stemmed large-head MoM-THA and recommend a restricted indication for hip resurfacing arthroplasty. Patients with implanted MoM-bearing should receive regular and standardized monitoring of metal ion concentrations. Further research is indicated especially with regard to potential systemic reactions due to accumulation of metal products.